(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines national customs related to child upbringing and their significance in the process of raising children, illustrated through the traditions of the Nurobod district. The importance of the child in Eastern culture is emphasized, where a child’s growth and development is regarded as the future of the entire nation. The article reveals these aspects based on ethnographic studies, analysis, and critical observations. In Eastern culture, the value of a human being has long been highly esteemed. Children were regarded as full-fledged individuals, and various customs were observed to ensure their harmonious development. These traditions were established not only to help the child grow into a well-rounded personality but also to instill a sense of love for the homeland. The article highlights these aspects as well. This study is based on ethnographic observation.